(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
Childhood Knew Grave Dangers That Threatened Its Security And Safety. Perhaps The Most Serious Of Which Is The Crime Of Forced Transfer Of Children, Which Is Considered A Form Of Genocide That Affected Innocence In Various Countries, And Led To A Disturbance Of World Order And Peace. The Crime By Recognizing The Individual Criminal Responsibility Of The Perpetrators And Inflicting The Most Severe Penalties. Key Words- Child, Genocide, Forcible Transfer Of Children